Does the use of the revised Psychosocial Assessment Tool (PATrev) result in improved quality of life and reduced psychosocial risk in Canadian families with a child newly diagnosed with cancer?. Issue 2 (4th September 2013) - Barrera, M.; Hancock, K.; Rokeach, A.; Atenafu, E.; Cataudella, D.; Punnett, A.; Johnston, D.; Cassidy, M.; Zelcer, S.; Silva, M.; Jansen, P.; Bartels, U.; et al.
Abstract Objectives Early psychosocial screening may guide interventions and ameliorate the adverse psychosocial effects of childhood cancer. The revised psychosocial assessment tool provides risk information – Universal (typical distress), Targeted (additional specific distress), and Clinical (severe distress) – about the child with cancer and his or her family. This pilot study investigated the benefits of providing a summary of family psychosocial risk information to the medical team treating the newly diagnosed child (Experimental Group, EG). Method We conducted a pilot randomized control trial with a sample of 67 parents, comparing the EG to the control group (CG) on parental perception of family psychosocial difficulties (revised psychosocial assessment tool risk levels), child behavior (behavior assessment scale for children‐2), pediatric quality of life (PedsQL), and parental anxiety (state‐anxiety scale of the state‐trait anxiety inventory ), 2–4 weeks after diagnosis (Time 1) and 6 months later (Time 2). Results Compared to the CG, participants in the EG had significantly reduced targeted and clinical risk (p < 0.001), and improved pain related PedsQL at Time 2 (p < 0.05). Scores for PedsQL total and nearly all subscales improved over time in both groups (p < 0.05 to p < 0.001). No changes in behavior scores were noted. Conclusion Preliminary findings suggest that providing a summary of the Psychosocial Assessment Tool to the treating team shortly after diagnosis may help reduce family wide psychosocial risk 6 months later and improve quality of life related to pain for children who are undergoing treatment for cancer. Copyright © 2013 John Wiley & Sons, Ltd.